Postpartum intrauterine contraceptive device – What influences its use? A qualitative study from Bengaluru urban district, India - Anissa Mary Thomas Thattil; Naveen Ramesh; Sobin Sunny; Sagnik Chakraborty; Sukesh Gerard; Francis Joseph Scaria; Archana Siddaiah (Indian Journal of Community and Family Medicine)
Introduction: The postpartum family planning program was introduced in 2009, and free services are being provided by the Government of India. However, the unmet need for family planning continues to be high in Karnataka (6.5%) with the unmet need for spacing at 3.8%. This may be due to a lack of understanding of the cultural, religious, and socioenvironmental factors in determining the utilization of postpartum intrauterine contraceptive devices (PPIUCDs) services. This study therefore attempted to understand factors which influence the acceptance of PPIUCD from the user, provider, and community perspectives in rural Bengaluru. Material and Methods: A qualitative study was conducted in the Government Taluk Hospital, Anekal, Bengaluru Urban District, Karnataka, India. Two focus group discussions and six key informant interviews were conducted, and data analysis was done using a thematic framework approach. The primary themes identified in our study were “client dependent,” “healthcare dependent,” and “solutions to the identified barriers.” Results: Two novel domains that emerged from the data analysis were that of “fear of side effects” and “family dynamics.” The attitude toward and use of PPIUCD was found to be the result of an interplay between the following: educational status, religion, misconceptions, fear of side-effects, poor reproductive autonomy, male child preference, increased client involvement, increasing women empowerment, and knowledgeable healthcare providers. Conclusion: The determinants of PPIUCD acceptance function at individual, family, and community levels. These need to be tackled to address the unmet need for family planning and spacing. Accurate information must be provided while simultaneously addressing the fears and misconceptions of clients.